Belgium : Selected Issues Paper. (IMF Staff Country Reports; Country Report, 2012)
This Selected Issues Paper on Belgium provides an overview of the extent of trade and financial openness of Belgium and the links to particular countries. With an export-to-GDP ratio of 79 percent, Belgium belongs to the most open economies in Europe and also globally. Its exports are highly concentrated with a share of three-fourths of total merchandise exports accounted for by the European Union, of which close to two-thirds go to Germany, France, and the Netherlands.